Pengaruh Belanja Langsung Dan Belanja Tidak Langsung Terhadap Pertumbuhan Ekonomi Kabupaten Badung 2001-2010 - Purnama Putra, I Gede Dwi; Adigorim, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2012)
This research is intended to determine whether partial simultaneouslyand there is significant influence between direct expenditure and indirect expenditure on economic growth in Badung regency in 2001-2010. Based of the results of the analysis are known, that there was a significant correlation between direct expenditure and indirect expenditure on economic growth in Badung regency in 2001-2010. Based on f –test statistic (simultaneously test) found that simultaneously direct expenditure and indirect expenditure have a significant effect on economic growth in Badung regency in 2001-2010 with a confidence level of 99 %.based on t-test (partial test) found that direct spending partiallyhas a positive and significant impact on economic growth at 95% confidence level.while partially indirect spending has a positive and significant impact on economic growth in Badung regency on the level of trust 99%.
Keywords: direct spending; economic growth; indirect spending